The Intertwining of Cultural Identity and Religious Identity in Church Musical Harmony for Social Harmony in Multicultural Societies - Lestari, Dewi Tika (UIN Sunan Gunung Djati Bandung, 2025)
Purpose: This study aims to show a creative approach to uniting the diversity of cultural and religious identities in musical harmony for efforts to build social harmony between multicultural and multireligious societies. Methodology: With an art-based qualitative analysis approach, this study analyzes elements of religious, cultural, and musical identities in the traditions and songs of the Maluku Protestant Church (GPM). Findings: This study found that GPM Songs have offered a new treasure in the tradition of religious songs by creatively and harmoniously combining elements of the cultural identity of the Maluku people who embrace all different religious identities through the shared language of pela-gandong, ain ni ain, kalwedo, in musical harmony for efforts to build and maintain social harmony in multicultural and multireligious societies. Implications: The findings of this study provide a new insight that can be applied to preserving peace in multicultural societies, namely that diverse cultural and religious identities can be harmonized through musical harmonization. Originality and Value: This study contributes to the discourse of music, rituals, and tradition studies, as well as multicultural and multireligious identities, and offers a new insight into creative diplomacy by using musical harmony in church song for social harmony.